Identification of Helicobacter pylori DNA in gallstones using Multiplex PCR - Shohreh Farshad; Abdolvahab Alborzi; Ali Malek Hossaini; Aziz Japooni; Barat Aboodi; Jalil Nasiri (Iranian South Medical Journal, 2006)
Background: Recent studies showed a possible relationship between infections caused by some of Helicobacter members and gallstones formation. The aim of this study was identification of Helicobacter members in gallstones from patients with biliary diseases. Methods: Gallstones and bile samples from 33 patients were subjected to rapid urease test, culture and Multiplex-PCR using primers based on 16s rRNA and isocitrate dehydrogenase genes to identify Helicobacter genus and H. pylori species genes, respectively. This PCR was also done on bile samples from 40 autopsied gallbladders with normal pathology (as a control group). Results: In 18.1% of stones and 12.1% of bile samples, H. pylori DNA was detected using PCR. Rapid urease and cultures tests were negative for all samples. The genome of H. pylori was not detected in control group using PCR. Conclusion: H. pylori DNA was detected in gallstone, however, we are not sure of H. pylori viability in these samples. To clarify the clinical role of Helicobacter in gallbladder diseases, more investigations are needed to ascertain whether this microorganism is innocent bystander or active participant in gallstone formation.